2020
DOI: 10.3390/sym12111794
|View full text |Cite
|
Sign up to set email alerts
|

Resting EEG Asymmetry Markers of Multiple Facets of the Behavioral Approach System: A LORETA Analysis

Abstract: Previously published models of frontal activity linked high relative left frontal activity to the behavioral approach system (BAS) and impulsivity. Additionally, these models did not account for BAS facets encompassing the anticipation of reward, i.e., goal-driven persistence (BAS–GDP) and reward interest (BAS–RI), from those that deal with the actual hedonic experience of reward, i.e., reward reactivity (BAS–RR) and impulsivity (BAS–I). Using resting electroencephalographic (EEG) recordings, the source locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 108 publications
(172 reference statements)
0
2
0
Order By: Relevance
“…Nine papers [6][7][8][9][10][11][12][13][14] were selected for publication: two literature reviews [7,9] and eight empirical studies [6,8,[10][11][12][13][14]. The articles were prepared by neuroscientists working in leading universities and research centers in Israel, Italy, Japan, Kazakhstan, the USA, and Russia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Nine papers [6][7][8][9][10][11][12][13][14] were selected for publication: two literature reviews [7,9] and eight empirical studies [6,8,[10][11][12][13][14]. The articles were prepared by neuroscientists working in leading universities and research centers in Israel, Italy, Japan, Kazakhstan, the USA, and Russia.…”
mentioning
confidence: 99%
“…V. De Pascalis et al, in the paper "Resting EEG Asymmetry Markers of Multiple Facets of the Behavioral Approach System: A LORETA Analysis" [10], performed cortical source analysis of resting electroencephalographic (EEG) recordings using eLORETA and found that a high behavioral approach system (BAS), except for impulsivity, was associated with greater relative left-sided activity in the superior frontal gyrus (BA10). Additionally, the authors used an isolated effective coherence (iCOH) analysis to correctly assess direct causal connections transmitting oscillatory information between cortical regions.…”
mentioning
confidence: 99%